The influence of the discovery learning model on students' mathematical creative thinking abilities in class VIII of SMP Negeri 1 Pematangsiantar - Ana Tasya Grace Adelina Sidabutar; Lois Oinike Tambunan; Yoel Octobe Purba (EDUCTUM: Journal Research, 2026)
This study aims to analyze the effect of the Discovery Learning learning model on the mathematical creative thinking ability of eighth grade students of SMP Negeri 1 Pematangsiantar. The study used a quantitative approach with a One-Shot Case Study design. The research sample consisted of 30 students selected through cluster random sampling techniques. Data were collected through a mathematical creative thinking ability test and a student perception questionnaire, which have been declared valid and reliable. Data analysis included normality and linearity tests, as well as hypothesis testing using simple linear regression and t-test. The results showed that the Discovery Learning model had a positive and significant effect on students' mathematical creative thinking ability, with a regression equation of Y = 9.100 + 0.313X. The significance value of 0.000 is less than 0.05 and the calculated t value (11.987) is more than the t table (2.048). The coefficient of determination of 83.7% indicates a very strong contribution. Thus, the Discovery Learning model is effective in improving students' mathematical creative thinking ability.